A note on the effects of start-up competitions: Experience from the Czech Business Plan Contest "Idea of the Year" - Ondřej Dvouletý (Journal of Innovation and Entrepreneurship, 2023)
The study contributes to the scholarly discussion on the effects of business plan competitions by assessing the survival and performance of the entrepreneurial teams participating in the Czech Business Plan Contest "Idea of the Year" during the years 2010-2015. The implemented research design followed up with the finalists, receiving financial and non-financial rewards 5 years after participating in the contest. The implemented scientific methods include mainly survival analysis and applied statistical techniques, such as cross-tabulations, tests of association, t-tests and correlation analysis. The obtained results allowed us to empirically support a hypothesis assuming that participation in the business plan contest positively relates to new venture creation, start-up survival, and performance. The study provides a series of recommendations for the contest's organizers, especially in terms of evaluation and monitoring and encouraging the projects' diversity. The added value for the international scholarship is that the article utilizes a complex theoretical framework combining various types of entrepreneurial capital that may be well used in future studies aiming to assess the impacts of start-up competitions.
Keywords: L26; H81; J68; L53; 650; Business plan competition; Czech Republic; Entrepreneurial ecosystem; Entrepreneurship and SME policy; Firm survival; Start-up contest